Non Decompressive Single Stage Bilateral Craniotomy in Traumatic Brain Injury - Sajid Khan, Akram Ullah, Muhammad Zubair, Arif Hussain, Tariq Jamal, Mumtaz Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: There is a substantial morbidity and mortality associated with traumatic brain injury (TBI). TBI still results in cerebral edema, which increases intracranial pressure (ICP) and reduces cerebral perfusion pressure (CPP) after traumatic brain injury (TBI). The purpose of this study was to evaluate the non-decompressive single stage bilateral craniotomy (SSBC) in traumatic brain injury. Patients and Methods: This prospective study was conducted on 44 TBI cases undergoing non decompressive single stage bilateral craniotomy (SSBC) in Neurosurgery Department of Prime Teaching Hospital, Peshawar from January 2022 to June 2022. All the patients underwent computed tomogram images and those fulfilling the inclusion criteria were enrolled. Demographic details, background parameters, measurement of intracranial pressure (ICP), and outcome were recorded. Results: Of the total 44 TBI patients, 32 (72.7%) were male and 12 (27.3%) were females. Age-wise distribution of patients were as follows: 3 (6.8%) in <20 years, 10 (22.7%) in 21-40 years, 16 (36.4%) in 41-60 years, 11 (25%) in 61-80 years, and 4 (9.1%) in >80 years. Glasgow comma scale at the time of admission and discharge were compared. Bilateral Csdh was the most prevalent diagnosis found in 16 (36.4%) patients followed by Bifrontal contusion 9 (20.5%), Bifrontal Edh with contralateral contusion 6 (13.6%), Bifrontal Edh 6 (13.6%), Bilateral temporal contusion 4 (9.1%), Unilateral Asdh with Contralateral Edh 2 (4.5%), and Bilateral Fronto-parietal Edh 1 (2.3%). Outcome of the non-decompressive SSBC in TBI were as follows: LAMA 5 (11.4%), discharged 28 (63.6%), Chest infection and tracheostomy 5 (11.4%), and expired 6 (13.6%) respectively. Conclusion: Our study concluded that male patients were more vulnerable to traumatic brain injury. Majority of the cases belonged to the age group 41-60 years. Non-decompressive single stage bilateral craniotomy is an effective, reliable, and economical procedure to manage traumatic brain injury patients. Single anesthesia along with single incision, shorter hospital stay, and postoperative management similar to unilateral procedure were the major advantages of non-decompressive SSBC. Keywords: Traumatic brain injury, Surgical treatment, Non-decompressive SSBC